Dumbeg Production Saintification in Rembang, Central Java, Indonesia : Local Culture Integration Efforts in Science Learning - Lestari, Wahyu; Sudarmin, Sudarmin; Sumarni, Woro (Journal of Innovative Science Education, 2022)
The purpose of this study was to reconstruct community science into scientific science in dumbeg production in Polandak village, Pancur District, Rembang Regency. The expected benefits in this study are to be used as an alternative source of contextual learning in schools, within the scope of science. The method used is descriptive qualitative through in-depth interviews, direct observation, and study of dumbeg production documentation. The focus of the research is the dumbeg production process from the preparation stage of the material, to the processing of materials. Data processing techniques in this study include analysis, verification, and the process of reconstructing community science into scientific science. The results of the study show that the scientific concepts contained in dumbeg production can be used as learning resources for science learning both at the elementary, middle and high school levels.